Application of the Group Investigation (Gi) Learning Model to Improve Learning Outcomes in Informatics Subjects Students Class Xi Sma Negeri 5 Seluma - Monica, Monica; Fitria, Yenni; Amdhi Yul, Fadlul (Jurnal Komputer Indonesia, 2024)
This research aims to determine the application of the group investigation (GI) learning model to improve learning outcomes in the informatics subject for class XI students at SMA Negeri 5 Seluma. This research method is a descriptive quantitative experiment. The design used is a one group pretest-posttest design. The subjects of this research were 31 students in class XI A of SMA Negeri 5 Seluma. The instrument used is 10 posttest questions and 5 pretest questions. The instrument has been tested for validity and reliability. The analysis techniques used are normality test, homogeneity test and hypothesis test. The results of the pretest with an average of 29 were in the very poor category, while the posttest with an average of 84 was very good and the results of student responses using a questionnaire with a validity test with a percentage of agreement or valid. The results of research using the paired sample test showed that the value was Sig.( 2-tailed) of 0.000 < 0.05 where t count > t table 12.449 > 2.042 so Ho is rejected Ha is accepted which means the group investigation (GI) learning model has a significant effect on the learning outcomes of class XI A students at SMA Negeri 5 Seluma